Catalytic abatement of CO over highly stable Pt supported on Ta2O5 nanotubes - Gonçalves, Renato V. (2014)
The development of active and stable catalysts has emerged as an important strategy in the catalytic abatement of CO. This article reports the use of the novel Pt-based catalyst supported on crystalline Ta2O5 nanotubes prepared by sputtering and anodization methods in CO oxidation reaction. Crystalline and amorphous Ta2O5 NTs and Pt modified sample were found active in low temperature CO oxidation. Results showed that active and highly stable Pt/Ta2O5 NTs catalyst could be a promising system for CO removal from gas exhaust.